Vacillation and performance: how alignment with environmental changes drives effective vacillation - Lee, MinJae (Academy of Management Proceedings, 2025)
Keywords: Empirical research; Environmental effect; Mechanism (biology); Period (music); dept.mgt

Developing entrepreneurship competence in STEM graduate students through a fellowship model - Wang, Zheni; Daneshmandi, Leila; Christodoulidou, Andri (Academy of Management Proceedings, 2025)
Keywords: Cognition; Competence (human resources); Entrepreneurship; Entrepreneurship education; Graduate students; Higher education; Mindset; Qualitative research; Value (mathematics); dept.mgt

Building positive experiences for sustainable development - Wang, Zheni; Zhu, Guorong; Zhang, Mengyi; Wang, Emma; Lv, Shuangning; Zheng, Jiawei; Shen, Yan; Steckler, Erica (Academy of Management Proceedings, 2025)
Keywords: Creativity; Face (sociological concept); Grounded theory; Stakeholder; Stakeholder engagement; Sustainability; Sustainable development; Work (physics); dept.mgt; dept.mrk

Museum experiences as innovative pedagogy in contemplative management education for sustainability - Yang, Charlie; Ivanova, Ekaterina; Ivanova, María (Academy of Management Proceedings, 2025)
Keywords: Contemplation; Curriculum; Environmental education; Experiential learning; Mindset; Reflective practice; Sustainability; Sustainable business; Visual arts education; dept.mgt

The relationship between quality management and innovativeness: an empirical study - Triana-Garcia, Randy; Muthuraj, Birasnav; Rincón-Guio, Cristian (6th South American Conference on Industrial Engineering and Operations Management, 2025)
This study aims to explore the relationship between four key elements of quality management: teamwork, feedback, motivational barriers, and need analysis, and their contribution to improve innovativeness in the Colombian educational context. Drawing on the concepts of control and learning in the quality management theory and using publicly available responses collected from the Colombian teachers who participated in the TALIS 2018 survey, this research study examines how teachers perceive these elements within their institutions and their potential impact on fostering innovativeness among teachers. The study adopts an empirical approach to analyze these relationships, employing a descriptive and inferential statistical framework to uncover patterns and correlations. By focusing on the school practices in Colombia, the research seeks to provide insights into how quality management practices can drive innovation in educational settings. Findings identify specific patterns in the implementation of these practices and their relationship with innovativeness among teachers, offering actionable recommendations for improving teaching strategies in education to improve quality. This study contributes to the broader understanding of management’s role in teaching and learning, offering valuable implications for policymakers and practitioners in developing countries. The novelty of this work lies in its analyses of TALIS data to assess quality management practices and their direct influence on fostering innovation.
Keywords: Business; Computer science; Empirical research; Knowledge management; Mathematics; Process management; Quality (philosophy); Statistics; dept.mgt

Bridging indigenous art and sustainability: transformative museum learning in management education - Yang, Charlie (Humanistic Management Journal, 2025)
Keywords: Bridging (networking); Computer science; Ecology; Environmental ethics; Indigenous; Pedagogy; Philosophy; Sociology; Sustainability; Transformative learning; dept.mgt

Rethinking Motivation and Reward Management: What We Know and Do not Know - Wang, Zheni (Edward Elgar Publishing Ltd., 2025)
This innovative book examines the controversial relationship between motivation and rewards from multiple theoretical and practical perspectives. It analyzes cutting-edge research on work motivation and reward management's economic and psychological roots and identifies future directions for advancement in the field. © Zheni Wang 2025.
Keywords: Compensation And Benefits; Motivation At Work; Reward Management; Self-Regulations; Total Rewards; Work Engagement; dept.mgt

Understand the Changes in Motivation at Work: Empirical Studies Using Self-Determination Theory-Based Interventions - Wang, Zheni; Briand, Mélanie (Behavioral Sciences, 2025)
Managers often need to stay motivated and effectively motivate others. Therefore, they should rely on evidence-based interventions to effectively motivate and self-motivate. This research investigated how self-determination theory-based interventions affect employees' motivation dynamics and motivational consequences within short time frames (i.e., within an hour, within a few weeks or months) in two empirical studies. Study one focused on assessing the effectiveness of a one-day training workshop in helping to improve managers' work motivation, basic psychological needs satisfaction/frustration, subordinates' motivation, and perceptions of managers' needs-supportive/thwarting behaviors within a few weeks. Results support the effectiveness of the training, as managers were rated by their direct subordinates as having fewer needs-thwarting behaviors and reported self-improvement in needs satisfaction and frustration six weeks after completing the training program. Study two used the mean and covariance structure analysis and tested the impact of three types of basic psychological needs-supportive/thwarting and control conditions (3 × 2 × 1 factorial design) on participants' situational motivation, vitality, and general self-efficacy for playing online word games within 30 min. Multi-group confirmatory factor analysis (CFA) confirmed the scalar measurement invariance, then latent group mean comparison results show consistently lower controlled motivation across the experimental conditions. During a quick online working scenario, the theory-based momentary intervention effectively changed situational extrinsic self-regulation in participants. Supplementary structural equation modeling (SEM; cross-sectional) analyses using experience samples supported the indirect dual-path model from basic needs satisfaction to vitality and general efficacy via situational motivation. We discussed the theoretical implications of the temporal properties of work motivation, the practical implications for employee training, and the limitations.
Keywords: Applied psychology; Autonomy; Computer science; Confirmatory factor analysis; Psychological intervention; Psychology; Self-determination theory; Situational ethics; Social psychology; Structural equation modeling; Work (physics); Work motivation; dept.mgt; employee training and development; motivation change; self-determination theory; theory-based interventions

Gender congruence and entrepreneurial investments: the role of others’ reactions - Wieland, Alice (International Journal of Gender and Entrepreneurship, 2025)
The purpose of this research is to explore the decision processes that underlie the gender gap in entrepreneurial investments. The present research explores how gender congruence with a sex-typed business opportunity influences anticipated reactions from others who may provide or withhold support and resources, how these affect the assessed probability of venture success and the amount the entrepreneur is willing to invest (WTI) in the opportunity.,A theoretical model is presented and empirically tested via path analysis. A pilot and an experimental study model explore how gender congruence influences entrepreneurial investment decisions. The experimental study uses a repeated measures design examining the experimental effects two sex-typed business opportunities crossed with participant gender (gender congruence) on anticipated others’ reactions, assessed probability of venture success and investment amount (WTI).,Gender congruence of a business opportunity influences anticipated others’ reactions, whether they will be supportive or not, of pursuing the opportunity. This in turn influences the estimated probability of success of the venture and the amount the prospective entrepreneur is willing to invest in it. These socio-cognitive decision processes reinforce the gender gap in entrepreneurship since participants anticipate less access to others’ support for gender incongruent opportunities. Although the mediational model indicates most proposed relationships and paths are invariant across genders, the exception was that women did not report higher WTI for the gender congruent venture.,The research applies the latest thinking in social psychology on gender norm violations to entrepreneurship, measuring how anticipated reactions from others are a factor in predicting estimates of venture success probability and self-investments.
Keywords: dept.mgt; peer-reviewed

The Impact of Attentiveness Interventions on Survey Data - Fuller, Christie; Simmering, Marcia; Waterwall, Brian; Ragland, Elizabeth; Twitchell, Douglas; Wall, Alison (Educational and Psychological Measurement, 2025)
Social and behavioral science researchers who use survey data are vigilant about data quality, with an increasing emphasis on avoiding common method variance (CMV) and insufficient effort responding (IER). Each of these errors can inflate and deflate substantive relationships, and there are both a priori and post hoc means to address them. Yet, little research has investigated how both IER and CMV are affected with the use of these different procedural or statistical techniques used to address them. More specifically, if interventions to reduce IER are used, does this affect CMV in data? In an experiment conducted both in and out of the laboratory, we investigate the impact of attentiveness interventions, such as a Factual Manipulation Check (FMC) on both IER and CMV in same-source survey data. In addition to typical IER measures, we also track whether respondents play the instructional video and their mouse movement. The results show that while interventions have some impact on the level of participant attentiveness, these interventions do not appear to lead to differing levels of CMV.
Keywords: Affect (linguistics); Applied psychology; Communication; Mathematics; Medicine; Post hoc; Psychological intervention; Psychology; Quality (philosophy); Social psychology; Statistics; Survey data collection; Survey research; dept.mgt; peer-reviewed